A VERSION APPLICATION FOR A CHILD OPPOSITE THE LAW - Zuliah, Azmiati; Silalahi, Dian Hardian; Putra, Adi; Sahputra, Rilawadi (Universitas Dharmawangsa Medan, 2022)
AbstractAll children are entitled to live, to grow, to thrive and to be protected from violence and discrimination. In reality, though, the number of children with legal problems increases significantly over the years. The treatment of children in trouble with the law suggests that they are often treated as